Outlook: Border Futures - On the path to a sustainable future for border regions - Karina Pallagst; Andrea Hartz; Beate Caesar (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
This outlook summarises the key findings of the Subsection and discusses them in the context of obstacles and opportunities as well as the future viability of cross-border cooperation.
urn:nbn:de:0156-40971966; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Cross-border cooperation; border regions; spatial development